Ambigüedades de la imagen en la cristianización del Perú: rento, los jesuitas y el Tercer Concilio * - Valenzuela Márquez, Jaime (2006)
In the context of contrarreforma catholic and the consolidation of the Andean colonization, it is examined the use missionary of the Christian images and the ambiguities of his adoption and interpretation. The subject is focused from the arrival of the jesuitas and, soon, under the emanated directives of third Concilio Limense. The author introduces itself, of this form, in one of the most suggestive subjects of Peruvian colonial history: the process of cristianización in centuries XVI and XVII.